The Development of an Application for The Management of ZISWAF at LazNas PHR - Ali, Fifitri; Zifi, Meliza Putriyanti; Yenas, Oscar (Politeknik Caltex Riau, 2024)
The advancement of information technology has revolutionized the way institions and agencies operate. To keep up this progress, LazNas PHR needed to develop an application for ZISWaf Management. The conventional reception process was inefficient and did not use the internet, resulting in delayed reports and distributions. A website based ZISWaf management application was created to streamline the acceptance, data collection, distribution, and report generation process. The development process included needs analysis, design, development, testing and conclusion drawing. The application was developed using the single-page application system development method and was tested through user acceptance tests. Results of the tests showed positive evolution, indicating that the application successfully assisted officers in managing the ZISWaf. Application has successfully integrated the use of information technology into the management of ZISWaf at LazNas PHR, contributing to the advancement and modernization of the institution